2017
DOI: 10.1177/1077558717692103
|View full text |Cite
|
Sign up to set email alerts
|

Medicare Advantage and Traditional Medicare Hospitalization Intensity and Readmissions

Abstract: Medicare Advantage plans have incentives and tools to optimize patient care. Therefore, Medicare Advantage hospitalizations may have lower cost and higher quality than similar traditional Medicare hospitalizations. We applied a coarsened matching approach to 2013 Healthcare Cost and Utilization Project hospital discharge data from 22 states to compare hospital cost, length of stay, and readmissions for Traditional Medicare and Medicare Advantage. We found that Medicare Advantage hospitalizations were substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
0
23
3
Order By: Relevance
“…4 The MA plans use various techniques to control health care utilization, such as restricted practitioner networks, prior authorization, and utilization review, as well as investing in preventive services, care coordination, and chronic disease management. [5][6][7][8][9] There is evidence that MA plans tend to enroll beneficiaries who are healthier than average, and comparisons that use beneficiaries with similar health profiles have found lower health service utilization among MA beneficiaries than among TM beneficiaries. [5][6][7][8] These results have been attributed, in part, to improved care coordination, chronic condition management, provision of low-intensity care, and transitions to less-expensive care settings in MA plans.…”
Section: Introductionmentioning
confidence: 99%
“…4 The MA plans use various techniques to control health care utilization, such as restricted practitioner networks, prior authorization, and utilization review, as well as investing in preventive services, care coordination, and chronic disease management. [5][6][7][8][9] There is evidence that MA plans tend to enroll beneficiaries who are healthier than average, and comparisons that use beneficiaries with similar health profiles have found lower health service utilization among MA beneficiaries than among TM beneficiaries. [5][6][7][8] These results have been attributed, in part, to improved care coordination, chronic condition management, provision of low-intensity care, and transitions to less-expensive care settings in MA plans.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported lower readmission rates in Medicare Advantage than traditional Medicare (7)(8)(9), leading some policy observers to conclude that Medicare Advantage beneficiaries have better post-acute care outcomes (10). However, these studies have been limited by the lack of complete and accurate data on hospitalizations in Medicare Advantage.…”
mentioning
confidence: 99%
“…2,8–10 There is remarkably little evidence about variation in the use of services in the Medicare Advantage (MA) program, which enrolled 31 percent of the Medicare population as of 2016. 11 While private managed care plans are required to provide all Medicare benefits (except for hospice care), they may have the potential to reduce unwarranted variations in care since these entities bear direct financial risk for the cost of services and have tools to constrain utilization that are not fully available in the traditional Medicare program.…”
mentioning
confidence: 99%